2016
DOI: 10.1002/mame.201500335
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Thermoset–Graphene Nanocomposites

Abstract: formaldehyde, phenol formaldehyde, silicone, vinyl ester, cyanate ester, unsaturated polyester resin, etc. The properties of thermoset materials can be further improved by reinforcing them with fi llers, most commonly used being clays, carbon nanotubes, and graphene nanoplatelets. GrapheneGraphene is a fundamental building block of all graphitic forms of carbon and consists of a single layer of sp 2 -hybridized carbon atoms arranged in a honeycomb structure. A single defect-free graphene layer has Young's modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 135 publications
1
26
0
3
Order By: Relevance
“…Previous work has shown that growth in hard segment content gives rise to an increase in tensile modulus, ultimate strength and yield strength, and a decrease in elongation at break . After adding each of the components to the PU, an increase in tensile strength was observed (Table ) that agrees with other published results …”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Previous work has shown that growth in hard segment content gives rise to an increase in tensile modulus, ultimate strength and yield strength, and a decrease in elongation at break . After adding each of the components to the PU, an increase in tensile strength was observed (Table ) that agrees with other published results …”
Section: Resultssupporting
confidence: 90%
“…[25,26] After adding each of the components to the PU, an increase in tensile strength was observed (Table 1) that agrees with other published results. [26][27][28]…”
Section: Mechanical Characterizationmentioning
confidence: 99%
“…Graphene is a single layer of graphite that has honeycomb lattice . Graphene has interesting properties such as high specific surface area (2,600 m 2 g −1 ) , enhanced modulus (1 TPa) , thermal conductivity (5,000 W mK −1 ) , and so on, which make it attractive for many applications especially in reinforcing polymeric nanocomposites . Yao et al , reinforced epoxy by 0.4 and 0.8 wt% functionalized graphene oxide (GO).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19] Unfortunately, GN sheets are prone to congregate in composites due to their strong -stacking between sheets and incompatible surface characteristics with the polymer matrices, hindering the application in nanocomposites. 13 Although many GN/polymer systems have been studied, [20][21][22] no literature is available for thermoset GN/UF nanocomposites.…”
Section: Introductionmentioning
confidence: 99%